Uma metodologia para a aprendizagem histórica de jovens estudantes do ensino fundamental por meio da produção de histórias em quadrinhos - Brito, André Domingos de (2020)
This academic work has as a goal to propose a methodology for the production of Comic Books aiming a meaningful historical learning for students in the Elementary School. Therefor, we sought to understand the conceptualization, definition and historicity of comic books and their relationship with teaching and learning in History; we also sought to present a debate about the insertion of the History´s workshop-class as a constructivist proposal for historical learning; and finally, it was indicate the elaboration of a History´s workshop-class through the construction of Comic Books that have as a criterion the mobilization of the language of these cultural artifacts and historical culture of the students from Elementary School. This research is turned to the knowledge’s referred the Historical Education, aiming looking to youngers from public school.